Analysis of COVID-19 Collective Irrationalities Based on Epidemic Psychology - Luo, Hua; Ren, Yu (Frontiers in Psychology, 2022)
As the SARS-CoV-2 virus swept the world in late 2019, it has brought widespread fear, some suspicion, and degrees of stigma. In the shadow of the COVID-19 pandemics, a series of collective irrationalities such as panic buying occurred. While there is no specific treatment for COVID-19, individuals and collectives respond rapidly to develop a routine, such as quarantine and isolation, making the prevention and control of COVID-19 become normalized and institutionalized and creating vaccines successfully in a short time. However, this situation also exposed a spectrum of problems triggered by lockdown, isolation, and vaccinations. This paper analyzes the COVID-19 collective irrationalities from epidemic psychology to provide a new reference view for overcoming psychological problems related to COVID-19.